2015
DOI: 10.1016/j.ssci.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate, perceived risk, and involvement in safety management

Abstract: a b s t r a c tThis article examines the relationship between safety climate, risk perception and involvement in safety management by first-line managers (FLM). Sixty-three FLMs from two French nuclear plants answered a questionnaire measuring perceived workplace safety climate, perceived risk, and involvement in safety management. We hypothesized that a positive perception of safety climate would promote substantial involvement in safety management, and that this effect would be stronger than the perceived-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 52 publications
7
46
0
4
Order By: Relevance
“…e sharing of experiences during training could help reveal the inconsistencies and di culties employees encounter in implementing hygienic and safety measures (time constraints, lack of sta and lack of resources) and could thereby increase perceived e cacy. is requires an open safety climate that supports and values safety-promoting actions and initiatives, encourages employees to make hygiene-and safety-related requests, and establishes a climate of trust (see Kouabenan et al 2015).…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%
“…e sharing of experiences during training could help reveal the inconsistencies and di culties employees encounter in implementing hygienic and safety measures (time constraints, lack of sta and lack of resources) and could thereby increase perceived e cacy. is requires an open safety climate that supports and values safety-promoting actions and initiatives, encourages employees to make hygiene-and safety-related requests, and establishes a climate of trust (see Kouabenan et al 2015).…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%
“…According to the collected data, frequent violating behaviors of supervisors in construction projects included authorizing processes that were not up to the standard, failing to enforce rules and regulations, authorizing workers to undertake dangerous construction works, and conducting supervision without qualifications. e front-line supervision will affect their workers' attitude and behavior towards safety [76]. In this study, "supervisory violations" had the associations with "adverse spiritual states" and "skill underutilization."…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, according to the respondents the rate if accidents and mishaps had also decreased since the implementation of the occupational safety and health policies. This finding is again evident from the study made by Moyo et al [40], Ndejjo et al [50] and Siziya et al [60], where the researchers too indicated reduction in occupational hazards and accidents after the implementation of the OSH policies. Again, from the challenges and opportunities of OSH implementation, the most important challenge was financial and lack of resources.…”
Section: Resultsmentioning
confidence: 79%
“…Safety climate is the apparent esteem put on well-being in an association at a specific point in time which are influenced by the opinions, attitudes, behaviors and other actions of the employees in an organization [50,51]. However, a safety climate of an organization is dependent on the characteristics and the safety practices of both the organization and the employees.…”
Section: Role Of Coaching In Development Of Safe Workplace Climatementioning
confidence: 99%